Zinc uptake by lowland and upland rice grown in tropical soil amended with burned rice husk and zeolites - Khayyambashi, Babak (2014)
There has been a dramatic increase in rice consumption over the past decade and therefore, one of the main considerations is enhancement of the quantity and quality of rice production at present. Application of soil amendments is an important method to improve rice yield. Although physicochemical properties of soil can be improved with soil amendments, Zn availability for plants will be declined due to the adsorption process. Zinc is an essential element for human and plant but too low or high concentrations can be problematic for human health and plant growth. Addition of soil amendment is a practice to restore physical, biological and chemical properties of soils. In Kedah and Perlis states of Peninsular Malaysia the application of burned rice husk into soils is common, but very little is known about the composition, quality and its effects on Zn availability for paddy plants. Therefore, this study was conducted to investigate the mechanisms of Zn sorption by burned rice husk and zeolite, to assess the concentrations of Zn, Fe and P in different parts of the submerged (var. 219) and upland rice (var. Tenom), and to evaluate the potential of burned rice husk and zeolite in reducing Zn uptake by paddy plants. The mineralogical composition of the zeolite samples were investigated by X-ray diffraction, and FT-IR spectra were used to elucidate the functional groups of the coco peat and burned rice husk. The detailed profiling of the elements presented on a particular surface was determined by SEM-EDX method. Specific surface area, total pore volume and pore diameter of all materials were determined by BET and BJH methods. A sorption study on Zn by organic (burned rice husk and coco peat) and inorganic (Iranian and Chinese zeolites) soil amendments were conducted to select the best adsorbent of Zn from each categories of amendments. The sorption data was fitted to the Langmuir and Freundlich adsorption models. The influence of acidity on Zn sorption by the selected adsorbents was also investigated at pH 5 and 7. A greenhouse experiment was conducted at Universiti Putra Malaysia during August and December 2012 using the selected adsorbents. A factorial randomized complete block design (RCBD) experiment was used with two soil amendments (Iranian zeolite (5% w/w) and BRH (2% w/w)) and five Zn rates (0, 2.5, 5, 10 and 20 mg kg-1) with 3 replications to determine the effects of the treatments on Zn uptake by MR219 (submerged) and Tenom (upland) paddy plant varieties in Kangar soil series. The data indicated that Iranian and Chinese zeolites contained 93.21 %, 58.83 % clinoptilolite-Na, respectively, but high amounts of tridymite (28.04 %) was also found in the Chinese zeolite. The results showed that the predominant functional groups on BRH were silicate and sulphonate groups while the amino, C-H, carboxylic (C=O), C=C, N-H, CH2 and C-O-H functional groups were the dominant in the coco peat. The Zn sorption isotherm data for both Iranian zeolite and Chinese zeolite were better fitted to the Langmuir model while for both coco peat and burned rice husk the Freundlich model fitted the sorption data better. It was found that the qmax of the Iranian zeolite was higher than the Chinese zeolite, and the affinity of burned rice husk for Zn adsorption was higher than coco peat. Hence, the burned rice husk and Iranian zeolite, which had higher adsorption rate of Zn, were selected for the subsequent experiment to evaluate their potentials in reducing Zn uptake by rice. The qmax value of Zn sorption was higher at pH 5 than 7 for both the Iranian zeolite and burned rice husk. However, the affinity of adsorption (KL) was the same for the Iranian zeolite at both pHs while for the burned rice husk it was higher at pH 7. In the green house study, the aerial dry biomass of both MR219 and Tenom were highest in soil amended with burned rice husk. There was no significant different in aerial dry biomass of both MR219 and Tenom planted in soils amended with Iranian zeolite and the control. However, the difference in Zn uptake by MR219 in the burned rice husk and Iranian zeolite amended soil was not significant. The increase in Zn rate increased the Zn in Y leaf of MR219 in all the treatments. The increase in the Zn rate decreased the concentration of Fe only in Y leaf, and similar trend was also observed for P concentration in Y leaf, leaf and stem. In general, Zn uptake by MR219 in zeolite and burned rice husk amended soils was lower than in the control plot at all Zn rates. The increasing Zn rate increased the Zn concentration in the Y leaf, leaf and stem of Tenom variety planted in the the control plot but in the amended plots, Zn concentration increased only in the leaf with the increasing Zn rate. The increase in the Zn rate decreased the concentration of P only in the leaf. The uptake of Zn by Tenom variety was lower in the amended soils than the control and the zeolite was better than the burned rice husk in reducing the Zn uptake by the Tenom variety. In conclusion soil amendment can be used to reduce Zn uptake by paddy plants. In addition, soil amendments can also increased the aerial dry biomass of the paddy plants. Burned rice husk was better than the Iranian zeolite in reducing Zn uptake and increasing aerial dry biomass of the paddy plants.